Diagnosis of Iron Deficiency in Inflammatory Bowel Disease by Transferrin Receptor-Ferritin Index. Issue 26 (July 2015) - Abitbol, Vered; Borderie, Didier; Polin, Vanessa; Maksimovic, Fanny; Sarfati, Gilles; Esch, Anouk; Tabouret, Tessa; Dhooge, Marion; Dreanic, Johann; Perkins, Geraldine; Coriat, Romain; Chaussade, Stanislas
Abstract : Abstract: Iron deficiency is common in patients with inflammatory bowel disease (IBD), but can be difficult to diagnose in the presence of inflammation because ferritin is an acute phase reactant. The transferrin receptor-ferritin index (TfR-F) has a high sensitivity and specificity for iron deficiency diagnosis in chronic diseases. The diagnostic efficacy of TfR-F is little known in patients with IBD. The aim of the study was to assess the added value of TfR-F to iron deficiency diagnosis in a prospective cohort of patients with IBD. Consecutive IBD patients were prospectively enrolled. Patients were excluded in case of blood transfusion, iron supplementation, or lack of consent. IBD activity was assessed on markers of inflammation (C-reactive protein, endoscopy, fecal calprotectin). Hemoglobin, ferritin, vitamin B9 and B12, Lactate dehydrogenase, haptoglobin, and soluble transferrin receptor (sTfR) were assayed. TfR-F was calculated as the ratio sTfR/log ferritin. Iron deficiency was defined by ferritin <30 ng/mL or TfR-F >2 in the presence of inflammation. One-hundred fifty patients with median age 38 years (16–78) and Crohn disease (n = 105), ulcerative colitis (n = 43), or unclassified colitis (n = 2) were included. Active disease was identified in 45.3%. Anemia was diagnosed in 28%. Thirty-six patients (24%) had ferritin <30 ng/mL. Thirty-two patients (21.3%) had ferritin levels from 30 to 100 ng/ml and inflammation: 2 had vitamin B12 deficiency excluding TfR-F analysis, 13 of 30 (43.3%) had TfR-F >2. Overall, iron deficiency was diagnosed in 32.7% of the patients. TfR-F in addition to ferritin <30 ng/mL criterion increased by 36% diagnosis rates of iron deficiency. TfR-F appeared as a useful biomarker that could help physicians to diagnose true iron deficiency in patients with active IBD.